PENGARUH PEMBAYARAN DIGITAL DAN LITERASI KEUANGAN TERHADAP PERSPEKTIF KINERJA KEUANGAN UMKM DI KOTA PANGKALPINANG - Indah Indah (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2024)
Indonesia has witnessed rapid development in the adoption of digital payment technology, particularly the Indonesian Standard Quick Response Code (QRIS), in recent years. The Bank Indonesia representative office for Bangka Belitung notes that the implementation of the Quick Response Code Indonesian Standard (QRIS) in Bangka Belitung continues to expand. Globally, the competitiveness of UMKMs can be seen, among other factors, from the aspect of technology application for finance (fintech) and the use of technology for marketing (digital marketing). The objective of this research is to determine the influence of digital payment usage on the perspective of financial performance, to understand the influence of financial literacy on performance perspective, and to ascertain the joint influence of digital payment usage and financial literacy on financial performance perspective. This research method employs a quantitative approach and an associative research type, which seeks relationships among several variables. The population of this study comprises all UMKM owners operating in Pangkalpinang City who have adopted Digital Payments, and those with varying levels of financial literacy. The sampling technique uses purposive sampling, and the sample size will be calculated using the formula for Unknown Populations. The sample is set at 100 samples. Data collection techniques include questionnaires, literature review, and interviews. Data analysis in this study is conducted using SPSS, including instrument testing, classical assumption testing, and hypothesis testing. The results show that digital payments influence the perspective of financial performance, financial literacy influences financial performance perspective, and digital payments and financial literacy simultaneously influence the financial performance perspective of UMKM in Pangkalpinang City.